Health policy and planning. (Oxford Oxford University Press)
Contains full text of articles, 1997- ; abstracts only, 1995-1996.
Keywords: Medical policy -- Developing countries -- Periodicals; Public health -- Developing countries -- Periodicals; Health planning -- Developing countries -- Periodicals